Aperture coupled microstrip antenna with different feed sizes and aperture positions - A. Rahim, Mohamad Kamal; Low, Zhi Wei; Soh, Ping Jack; Asrokin, A.; Jamaluddin, Mohd. Haizal; Masri, Thelaha (2006)

(untitled)
The aperture coupled is one of the feeding techniques in micrsotrip antenna. The main mechanism of power transfer between its feed line and patch is the coupling mechanism. This paper describes two different designs of an aperture coupled microstrip patch antenna fabricated using different feed width, aperture size and position. In both proposed structures, the feed width of aperture coupled microstrip antennas (ACMAs) and aperture position are varied, while keeping tight to the three layer structure visible in conventional ACMAs (feed line at bottom most layer, ground plane with aperture in middle layer and patch layer at the top). The fabricated antenna produced better return loss and impedance bandwidth, while maintaining comparable radiation performance compared against simulation. All antennas produced maximum E- and H-plane co- and cross-polarization difference in the magnitude of -20dB and half-power beam widths (HPBW) of 90deg.